Analyzing the Impact of Federal Reserve Policy on Economic Stability in the Last Five Years - Horshkov, Bogdan; Ali, Tanweer; Pavelka, Tomáš, 1975-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis comprehensively analyzes the Federal Reserve's macroeconomic impact on the US economy's stability. This study applies quantitative research methodologies to assess the influence of monetary policy tools, such as the federal fund rate and quantitative easing volume, on crucial economic stability indicators, including GDP, inflation, and unemployment, during a period marked by significant challenges, including the COVID-19 pandemic. The research delves into the relationship between critical monetary policy tools and economic stability indicators. The analysis provides vital insights into the current state of the U.S. economy and the impact of the Federal Reserve in setting its direction. The study concludes by offering a series of policy recommendations to improve the efficacy of Federal Reserve policies in fostering future economic stability. This suggests potential areas for future research that can enhance our comprehension of the intricate relationship between monetary policy and financial outcomes.
Vedoucí práce: Tanweer Ali
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses